2022
DOI: 10.3390/jcm11051170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence, and Outcomes of Hyperkalaemia in Patients with Chronic Heart Failure and Reduced Ejection Fraction from a Spanish Multicentre Study: SPANIK-HF Design and Baseline Characteristics

Abstract: Hyperkalaemia is a growing concern in the treatment of patients with heart failure and reduced ejection fraction (HFrEF) as it limits the use of some prognostic-modifying drugs and has a negative impact on prognosis. The objective of the present study was to estimate the prevalence of hyperkalaemia in outpatients with HFrEF and its impact on achieving optimal medical treatment. For this purpose, a multicentre, prospective, and observational study was carried out on consecutive HFrEF patients who were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
0
1
Order By: Relevance
“…First of all, the present study analyzed a sample consisting of a higher proportion of males (76.6%) as compared to females (23.4%). Nevertheless, this gender distribution is consistent with previous studies conducted in similar settings, which have reported comparable figures ranging from 70% to 78% [12,21,48]. It is also important to mention that the present investigation is a retrospective observational study, and it is important to note that our operational definition of hyperkalemia diverges from the definition employed in clinical practice guidelines and the majority of previous research (potassium > 5.0 mEq/L) [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First of all, the present study analyzed a sample consisting of a higher proportion of males (76.6%) as compared to females (23.4%). Nevertheless, this gender distribution is consistent with previous studies conducted in similar settings, which have reported comparable figures ranging from 70% to 78% [12,21,48]. It is also important to mention that the present investigation is a retrospective observational study, and it is important to note that our operational definition of hyperkalemia diverges from the definition employed in clinical practice guidelines and the majority of previous research (potassium > 5.0 mEq/L) [20].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of baseline hyperkalemia in our study (2.4%) was lower than in previously published registries (4.3% [12] and 5.7% [21]). Since the baseline characteristics of the patients were similar in all three studies, the main observed differences may be explained by the higher percentage of individuals that received ACEI/ARB/ARNI (92% in the ESC-EORP-HFA Heart Failure Long Term study, 94% in the SPANIK-HF and 79% in our study) and MRA (73% versus 63.8% in the mentioned registries, and 58.4% in our sample), since these patients were under follow-up in specialized units in the drug titration phase [12] or had completed titration [21], while our patients were starting follow-up in such a unit for the first time. The high incidence of hyperkalemia in the first year of follow-up in our population, in comparison to subsequent years, could be explained by the fact that it is in the first months after patient referral when the progressive titration of neurohormonal treatment takes place.…”
Section: Discussioncontrasting
confidence: 89%